If God still breathes, why can't I?: Black Lives Matter and biblical authority - Parker, Angela N. (Wm. B. Eerdmans Publishing Co., 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by Lisa Sharon Harper -- Preface -- Acknowledgments -- Introduction: What Is Your Relationship to the Bible? -- 1. Stifled Breathing: Trained to Be a White Male Biblical Scholar -- 2. White Supremacist Authoritarianism Is Not God's Breath -- 3. Stop Gaslighting Me -- 4. Moving from Stifled Breath to Full-Throated Faith -- Conclusion: Breathing Womanist Air -- Appendix -- Bibliography.